2012
DOI: 10.1177/0034355212469839
|View full text |Cite
|
Sign up to set email alerts
|

Empirically Derived Test Specifications for the Certified Rehabilitation Counselor Examination

Abstract: This study examined the major job functions and knowledge domains required for effective rehabilitation counseling practice in today's rapidly changing practice environment to revise and update the test specifications for the Commission on Rehabilitation Counselor Certification examination. This report describes the methodology used in this nationwide study, the primary research questions addressed, the study's principal findings and recommendations, including the new set of test specifications that will guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 15 publications
2
40
1
Order By: Relevance
“…Findings from the Leahy et al (2013) study provided a strong empirical support for the certification processes as well as information to guide the development of test specifications for the CRCE process. However, more than 5 years have passed since the most recent study completed in 2012 (Leahy et al, 2013). Over the past several years, enormous changes have taken place in the rehabilitation counseling profession, including the merger between CORE and CACREP on July 1, 2017 (CACREP, 2015).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Findings from the Leahy et al (2013) study provided a strong empirical support for the certification processes as well as information to guide the development of test specifications for the CRCE process. However, more than 5 years have passed since the most recent study completed in 2012 (Leahy et al, 2013). Over the past several years, enormous changes have taken place in the rehabilitation counseling profession, including the merger between CORE and CACREP on July 1, 2017 (CACREP, 2015).…”
mentioning
confidence: 86%
“…Measures KVI-R. The KVI-R developed by Leahy et al (2013) was used as the primary instrument for the study. The current version of the KVI-R was first carefully reviewed and revised through a Delphi study with a panel of subject matter experts before being distributed for the study.…”
mentioning
confidence: 99%
“…Unfortunately, no studies exist examining specifically how MRC and OM counselors differ with respect to pre-service training. Studies have examined the required knowledge areas of rehabilitation counselors (Leahy et al, 1993(Leahy et al, , 2003, and have compared how these knowledge areas differ by licensure type (Leahy et al, 2012), but none have specifically examined if MRC and OM counselors differ in the amount of training received in these areas. Therefore, as the first step in an exploration of the reasons for the similar closure rates, it is important to examine precisely how the pre-service training experiences of these counselors differ to determine the unique skillset MRC counselors possess.…”
Section: Introductionmentioning
confidence: 99%
“…Despite variability in study sample and country/continent of location, the areas of training need reported by Taiwanese study participants are largely in congruence with those identified by American professionals (Leahy et al, 2013;Leahy et al, 2009), Japanese job coaches and job placement specialists (Yaeda, Kundu, & Nishimura, 2013), and Australian and German VR practitioners (Matthews et al, 2015). Therefore, in view of the above findings, it can be stated that professional development programs designed for current and future rehabilitation counselors in the United States and other countries need to incorporate the areas of training need identified by Leahy et al (2009), Yaeda, Kundu, and Nishimura (2013), Matthews et al (2015), and in the present study.…”
Section: Implications For Rehabilitation Counselor Educations In Taiwanmentioning
confidence: 70%